Guidelines and Standards for Wireless Technology for Individuals with Hearing Loss - Thibodeau, Linda M.; Wallace, Sarah (Seminars in Hearing, 2014)
It is important that hearing assistance devices/systems (HADS) be evaluated electroacoustically to verify performance relative to published results and to compare performance across similar devices. The guidelines for verification prepared by professional organizations address the comparison of the HADS to personal amplification systems. The current document by the American Academy of Audiology includes guidelines for wireless systems integrated with hearing aids, classroom audio distribution systems, and induction loop systems. A new standard by the American National Standards Institute (ANSI) is now available, which provides specifications for systematic electroacoustic measurements that can be compared across manufacturers. Although many of the measurements are similar to those in the ANSI Standard for the Electroacoustic Evaluation of Hearing Aids, there are recommendations regarding position of wireless microphones and receivers that are specific to procedures for the evaluation of HADS. The ANSI standard for Electroacoustic Evaluation of HADS will be reviewed with particular application to systems with wireless transmitters and receivers.
Keywords: Assistive technology; hearing impaired; verification